AstroBioChemistry in harsh environments: study of polycyclic aromatic hydrocarbons in active galaxies - Sales, Dinalva Aires; Canelo, Carla M. (Cadernos de Astronomia, 2022)
Active galaxies (AGNs) are those in which supermassive black-holes (SMBHs) in their core are capturing matter through an accretion disk. Within the paradigm of AGNs, a point still under debate originates this activity, from what mechanism causes it to how does it affect dust and molecules in galaxies. In order to advance our knowledge in this question, one must conduct studies on the origin and feeding of SMBHs in AGNs through molecular emissions in galaxies, such as OH Megamaser galaxies (OHMGs), Seyfert and Starburst galaxies. This work shows that, in AGNs, organic molecules of polyciclic aromatic hydrocarbons (PAHs) are larger (>180 carbon atoms) than in galaxies with star formation region. This fact implies that PAHs survive the intense radiation and evolve throughout the evolution of the universe, where they grow and incorporate nitrogen. These polyciclic aromatic nitrogen heterocycles (PANHs), which can vary the PAH band emission at 6.2 micrometers, can provide the missing link between the biochemistry of PAHs, seen in the gas and dust of galaxies, and the nucleobases that constitute the coding machinery of life on Earth.
Keywords: extragalactic astronomy; astrobiology; astrochemistry; active galactic nuclei